CPT Encapsulated Silica-titania Hollow Nanoparticle Targeting SK-BR-3 Cells for efficient Anticancer treatment. Issue 1725 (24th February 2015) - Jang, Yoonsun; Jang, Jyongsik
ABSTRACT: HER-conjugated hollow nanoparticles (HER–HNP, ca. 50 nm in diameter) are fabricated using a dissolution and re-deposition method and used to encapsulate camptothecin (CPT). The HER-HNP-CPT is used as an anti-cancer agent for human breast cancer SK-BR-3. It has excellent mono-dispersity and a high loading efficiency for CPT. Two kind of cell lines are used in this study; SK-BR-3 and RAW 264.7. SK-BR-3 and RAW 264.7 are used as targeting and controlling cell line, respectively. When SK-BR-3 cells are treated with HER-HNP-CPT, the viability decreased to 55%, which is ca. 1.5 times higher anti-cancer efficiency in comparison to RAW 264.7. The HER-HNP-CPT system offers a new opportunity to facilitate implementation of a hydrophobic drug for effective anti-cancer treatment of SK-BR-3 cells.